Natural ventilation and energy efficiency of a building envelope in tropical climate - Wu, Xiaoying (2014)
With the development of economy, environmental issues become more critical. Improving building energy efficiency is one of the key solutions to reduce the environmental pollution. Building envelopes as a major component in building design play a very essential role in building energy efficiency. In general, the building envelopes separate the indoor and outdoor, and perform as a protection layer of living space from the extreme harsh environment. Apart from the protection function, the building envelopes should be aesthetic and energy efficient at the same time. Natural ventilation is a very commonly-used traditional strategy to achieve human comfort and energy saving simultaneously. With the development of technology, currently various building forms can be built in reality. This gives natural ventilation more potential in application. Therefore, the effect of building forms on natural ventilation becomes very important for architects and developers. In the present thesis, the academic contributions into the research area of building performance in energy efficiency are achieved in the following two aspects. Modeling and Simulation of Natural Ventilation for Effect of Building Forms • Regarding the structured building, it is found that common space achieves the poorest natural ventilation over a year, excluding rooftop. This is attributable to the low porosity of building. • Regarding the porous building, it is concluded that, with the increase of the percentage of void inside the building, common spaces results in higher wind speed, and the percentage of thermal comfortable area also increases, contrary to structured building. • Regarding the free-form architecture building, it is observed that the wind velocity profile inside the atrium is highly correlated to the floor level. This is attributed to the stack effect. In addition, the internal airflow speed is almost independent of the external wind. Modeling and Simulation of Energy Efficiency for Effect of Building Envelope • In terms of external building envelope, a reduction in cooling load is achieved by increasing either the vertical length L, or by reducing the horizontal distance D between building envelope and wall. • It is shown that a maximum energy efficiency of 13% is achieved by increasing length L to 50% of the building height H. • In general, the external envelope tends to make a more significant contribution to improvement of energy efficiency for buildings with windows, compared with windowless building.